Effect of β lactam antibiotic use in children on pneumococcal resistance to penicillin: prospective cohort study - Nasrin, Dilruba (BMJ, 2002)
OBJECTIVE: To examine the relation between use of antibiotics in a cohort of preschool children and nasal carriage of resistant strains of pneumococcus. DESIGN AND PARTICIPANTS: Prospective cohort study over two years of 461 children aged under 4 years living in Canberra, Australia. MAIN OUTCOME MEASURES: Use of drugs, respiratory symptoms, and visits to doctors were documented in a daily diary by parents of the children during 25 months of observation. Isolates of pneumococci, which were cultured from nasal swabs collected approximately six monthly, were tested for antibiotic resistance. RESULTS: From the four swab collections 631 positive pneumococcal isolates from 461 children were found, of which 13.6% were resistant to penicillin. Presence of penicillin resistant pneumococci was significantly associated with children's use of a β lactam antibiotic in the two months before each swab collection (odds ratio 2.03 (95% confidence interval 1.15 to 3.56, P=0.01)). The odds ratio of the association remained >1 (though did not reach significance at the 0.05 level) for use in the six months before swab collection. The association was seen in children who received only penicillin or only cephalosporin antibiotics in that period. The odds ratio was 4.67 (1.29 to 17.09, P=0.02) in children who had received both types of β lactam in the two months before their nasal swab. The modelled odds of carrying penicillin resistant pneumococcus was 4% higher for each additional day of use of β lactam antibiotics in the six months before swab collection. CONCLUSIONS: Reduction in β lactam use could quickly reduce the carriage rates of penicillin resistant pneumococci in early childhood. In view of the propensity of these organisms to be spread among children in the community, the prevalence of penicillin resistant organisms may fall as a consequence.